EVALUASI DESAIN SPINDEL VMC 500 DENGAN PERANGKAT LUNAK ELEMEN HINGGA - Ayudia Erwin, Dini
This final project evaluates a model of spindle VMC 500, which is one of milling machine components. When making a component of a machine, the error values should be really small because this value can affect other manufacturing products. To validate this project, the analysis also considered data from static, thermal, and dynamic examinations of spindle VMC 250, than simulated them using finite element software Ansys®. Then, spindle VMC 500 was simulated with the same software to get data of total deflection, distribution of temperature, and natural frequencies. From these simulations, it is shown that total deflections for each direction X, Y, and Z are 21?m, 17 ?m, and 84 ?m. These total deflections are mostly affected by the thermal change, so for the cooling design, it can be optimized by adding more coolant chanels. Furthermore, deflection caused by dynamic effect didn’t affect this design because the natural frequencies happened at 8640 rpm or above spindle’s range of work. The analytical process has produced information of the worthiness of the spindle VMC 500 to be a real product as the component of a milling machine. Hopefully, this project could be a reference for a machine tools production technology, especially in Indonesia.